The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1992
DOI: 10.1038/358591a0
|View full text |Cite
|
Sign up to set email alerts
|

The catalase—peroxidase gene and isoniazid resistance of Mycobacterium tuberculosis

Abstract: Tuberculosis is responsible for one in four of all avoidable adult deaths in developing countries. Increased frequency and accelerated fatality of the disease among individuals infected with human immunodeficiency virus has raised worldwide concern that control programmes may be inadequate, and the emergence of multidrug-resistant strains of Mycobacterium tuberculosis has resulted in several recent fatal outbreaks in the United States. Isonicotinic acid hydrazide (isoniazid, INH) forms the core of antitubercul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
793
2
11

Year Published

1994
1994
2009
2009

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,194 publications
(821 citation statements)
references
References 16 publications
15
793
2
11
Order By: Relevance
“…As linhagens MDR surgem após uma seqüência de mutações nos diferentes genes envolvidos com cada um dos fármacos. 45 Os avanços em biologia molecular tornaram possí-vel investigar os mecanismos genéticos da resistên-cia aos fármacos, bem como caracterizar as mutações relacionadas à resistência aos diversos fármacos. Entretanto, ainda há mecanismos bem mais complexos a ser esclarecidos, como a resistência à isoniazida.…”
Section: As Bases Moleculares Dos Mecanismos De Resistênciaunclassified
“…As linhagens MDR surgem após uma seqüência de mutações nos diferentes genes envolvidos com cada um dos fármacos. 45 Os avanços em biologia molecular tornaram possí-vel investigar os mecanismos genéticos da resistên-cia aos fármacos, bem como caracterizar as mutações relacionadas à resistência aos diversos fármacos. Entretanto, ainda há mecanismos bem mais complexos a ser esclarecidos, como a resistência à isoniazida.…”
Section: As Bases Moleculares Dos Mecanismos De Resistênciaunclassified
“…Isoniazid is a synthetic pro-drug that requires the product of the katG structural gene for its activation (Telenti & Iseman 2000); this drug becomes an active compound once it is metabolized by the M. tuberculosis catalase-peroxidase enzyme, and inhibits the activity of the enoyl-ACP (CoA) reductase enzyme (encoded by the inhA gene) in the presence of NADH or NAD + (reviewed in , Schroeder et al 2002. Resistance to isoniazid is more complex, as it involves at least 4 genes: katG, which mediates both susceptibility and resistance to isoniazid, and encodes the catalase-peroxidase enzyme; inhA, which is involved in the elongation of fatty acids (Zhang et al 1992); ahpC, which encodes the hydroperoxide alquil reductase C; and oxyR, which is an important regulator of oxidative stress (Telenti & Iseman 2000).…”
Section: Mechanism Of Drug Action and Mdr/xdrmentioning
confidence: 99%
“…Isonicotinic acid hydrazide (isoniazid [INH]) has been a potent and clinically important antituberculosis drug since its introduction in 1952 (2), but the emergence of INH-resistant mutants has limited its efficacy (10). While neither the mode of action nor the cellular target of INH has been elucidated, it has been suggested that peroxides and peroxidases are needed to activate INH (14,17) and that the in vivo target may be mycolic acid synthesis (5,15).…”
mentioning
confidence: 99%